Abdominal pseudotumor secondary to surgical obliteration - Espinosa, Gabriela; Irigoyen, Virginia; Pontillo, Mauricio; Rodríguez Temesio, Gustavo (Cirugía del Uruguay, 2020)
Obliteration or foreign body retention after a surgical procedure is a real, current, and preventable problem that affects the safety of the surgical patient. We present the case of a 42-year-old patient, who underwent an emergency laparotomy cholecystectomy 3 years ago, who consulted for a pain-free, progressing growth-free one-year central-abdominal tumor with no changes in transits. It is intra-abdominal, rounded 10 cm in diameter. A tomographic study was requested to confirm the finding, and the exploration was decided by means of a laparotomy that confirmed the presence of a surgical pad. The patient evolves favorably. It is important to adopt a culture of prevention, through the perioperative surveillance of the materials and instruments used during the surgical act. Oblite can occur in any procedure and provoke medico-legal actions against the treating team.